(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2012)
Activated carbon was prepared using bio-diesel waste (Jatropha seedcake) by conventional carbonization followed by steam activation process on a laboratory scale. Preliminary tests were conducted to investigate the influences of different operating parameters, such as initial material size, pyrolysis temperature and hold time on the properties of pyrolized chars. To determine the optimum conditions for producing activated carbon, the effect of activation temperature and activation time have been studied. The maximum BET surface area of 613.43 m2/g and highest methylene blue adsorption capacity of 8.27 mg/g was obtained at a pyrolysis temperature of 600°C for hold time 1.5 hr followed by steam activation at a temperature of 800°C for a hold time of 1 hr. The produced activated carbon was almost like ash at 900°C. FT-IR and TG/DTA have been done in order to understand the structural changes during the process. The waste material was a suitable raw material for the production of good quality activated carbon. DOI: http://dx.doi.org/10.3329/bjsir.v47i3.13056 Bangladesh J. Sci. Ind. Res. 47(3), 257-264, 2012